Association of the genetic variation of (MSX1-7) and non syndromic cleft lip palate in Chilean subjects - Blanco, R; Jara, L; Villaseca, M C (Revista medíca de Chile, 1998)
Homeotic genes have regulatory functions during development. It has been postulated that the human Msx-1 homeotic gene can be involved in the etiology of non syndromic cleft lip palate, since its homologous Msx-1 is involved in cleft palate of mice. To perform an association analysis between the genetic variation of Msx-1 and non syndromic cleft lip palate in Chilean subjects. Seventy patients with non syndromic cleft lip palate, 136 healthy relatives of these patients and 69 non related normal individuals were studied. CA microsatellite in Msx-gene, that was amplified with PCR, was studied. No differences in the genetic frequencies of Msx-1 alleles, were observed in the three groups studied. Allelic heterogeneity for allele 2 seems to be related to cases of non syndromic cleft lip palate from multiplex families and heterogeneity for allele 3 is related with simplex families cases. These results seem to support the hypothesis of genetic heterogeneity in the etiology of non syndromic cleft lip palate.